Lithium-rich antiperovskite (Li2Fe)SeO: a high-performance cathode material for lithium-ion batteries - Mohamed, M. A. A.; Singer, Lennart; Hahn, Hannes; Djendjur, Denis; Özkara, Attila; Thauer, Elisa; González Martínez-País, Ignacio; Hantusch, Martin; Büchner, Bernd; Hampel, Simon; Klingeler, Rüdiger; Gräßler, Nico (Journal of power sources, 2023)
Lithium-rich antiperovskite cathode materials with cationic and anionic redox bi-functionality are promising candidates for lithium-ion batteries (LIB) with high energy density. Here, we report the synthesis of antiperovskite (Li2Fe)SeO by means of an one-step solid-state method which results in phase pure material consisting of predominantly micrometer-sized particles. Thermodynamic investigations confirm high thermal stability of (Li2Fe)SeO up to 1200 °C without any indication of phase decomposition. Electrochemical studies of (Li2Fe)SeO-based cathodes show a multi-step redox process involving electrochemical activity of cationic Fe and anionic Se. Rate capability tests yield a discharge capacity of 150 mAh g−1 and 100 mAh g−1 at 0.1 C and 1 C, respectively. In-depth kinetic analyses by in-situ electrochemical impedance spectroscopy indicate a considerable structural change primarily in the first cycle, however, the structure stabilizes afterwards in the following cycles. Accordingly, we observe superior high cycling stability. Upon cycling, the material displays only a slight capacity fading while still delivering 140 mAh g−1after 100 cycles at 0.1 C. Our findings highlight the high performance and compelling cycling stability of (Li2Fe)SeO as cathode material in lithium-ion batteries.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 17.04.2023